1997
DOI: 10.1007/bf02238766
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neutrophil cytoplasmic antibody in patients with systemic lupus erythematosus is unrelated to clinical features

Abstract: To investigate the incidence, the specificity and clinical significance of positivity for serum anti-neutrophil cytoplasmic antibody (ANCA) in 31 patients with systemic lupus erythematosus (SLE), the indirect immunofluorescence (IIF) technique and enzyme-linked immunosorbent assay (ELISA) were used to measure ANCA. Purified myeloperoxidase (MPO), lactoferrin (LF), cathepsin-G (CTG) and elastase (HLE) served as ANCA antigens for ELISA. Thirteen (42%) of the 31 SLE patients showed positivity for perinuclear, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 17 publications
0
34
0
1
Order By: Relevance
“…ANCA seropositivity was associated with the presence of nephritis, particularly LN IV, as well as anti-dsDNA antibodies (17). Other reports have failed to show a correlation between ANCA and clinical features or organ involvement (14,18,19).…”
Section: Discussionmentioning
confidence: 91%
“…ANCA seropositivity was associated with the presence of nephritis, particularly LN IV, as well as anti-dsDNA antibodies (17). Other reports have failed to show a correlation between ANCA and clinical features or organ involvement (14,18,19).…”
Section: Discussionmentioning
confidence: 91%
“…A negative correlation has been reported between the presence of ANCA and nephritis [15,16], specific renal pathologic findings, renal prognosis, mortality [4,17], and vasculitis [15]. On the other hand, Ecklund et al [7] found a relation to the presence of nephritis.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have demonstrated no correlation between ANCA and the activity of SLE [2,14,15]. On the other hand, its association with relapse [16] or disease activity has also been reported [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANCA directed against various neutrophil cytoplasmic constituents have been demonstrated by antigen-speci®c assays, but the antigens responsible for ANCA reactivity in SLE have still not been fully determined and the role of ANCA in SLE remains unclear. Moreover, reports are controversial concerning their clinical relevance [10,11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%